An analysis of students' mathematical understanding in polyhedral geometry - Hafizah Syahrani Subekti; Atma Murni; Yenita Roza (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Mathematical understanding is a fundamental component of mathematics learning, as it underpins the development of other essential mathematical competencies. However, many students tend to rely on memorizing formulas without achieving a deep conceptual understanding. This study aimed to analyze students' mathematical understanding in the topic of three-dimensional shapes with flat surfaces at the junior high school level. A descriptive qualitative approach was employed, involving 25 students from SMP Negeri 12 Pekanbaru as research participants. Data were collected through two open-ended test items and semi-structured interviews, and analyzed using indicators of mathematical understanding, including restating concepts, applying procedures algorithmically, and connecting concepts within and beyond mathematics. The results showed that the majority of students (76%) demonstrated a low level of mathematical understanding, while 12% were classified as having moderate understanding and 12% as having high understanding. Students in the high category were able to fulfill all indicators, whereas those in the moderate and low categories experienced difficulties, particularly in applying procedures algorithmically and establishing conceptual connections. These findings indicate the need for instructional practices that emphasize conceptual understanding and support students in meaningfully connecting mathematical concepts to problem-solving contexts.